2022
DOI: 10.3390/molecules27113428
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Allelopathic Potential of Lemna minor L. Obtained from a Shallow Eutrophic Lake

Abstract: Allelopathy is an interaction that releases allelochemicals (chemicals that act allelopathically) from plants into the environment that can limit or stimulate the development, reproduction, and survival of target organisms and alter the environment. Lemna minor L. contains chemicals that are allelopathic, such as phenolic acids. Chemical compounds contained in L. minor may have a significant impact on the development and the rate of multiplication and lead to stronger competition, which may enhance the allelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This enables them to quickly cover any open-water space available to them and consolidate their areas of dispersion by forming multi-layered mats. Their rapid, surface-covering growth can deprive other photosynthetic aquatic organisms of space, light, and nutrients, thus diminishing their competitive ability (see [132]). This is illustrated by the designation of La.…”
Section: Competitionmentioning
confidence: 99%
“…This enables them to quickly cover any open-water space available to them and consolidate their areas of dispersion by forming multi-layered mats. Their rapid, surface-covering growth can deprive other photosynthetic aquatic organisms of space, light, and nutrients, thus diminishing their competitive ability (see [132]). This is illustrated by the designation of La.…”
Section: Competitionmentioning
confidence: 99%
“…However, since greater biomass production was observed for both L. minor and S. molesta when in co-culture, a possible explanation could be the presence of a substance with an allelopathic effect in the growth media, which can limit or stimulate the development, reproduction, and survival of target organisms [58,59]. Studies have reported the allelopathic potential of L. minor plants, showing, however, the negative effects of the allelochemicals produced by these plants [59,60]. Similarly, negative allelopathic effects have been described for S. molesta plants [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in view of the common phenomenon wherein some plants may produce allelopathic substances that inhibit the growth of other plants, duckweed may also be one of these plants. Contemporary researchers have discovered that duckweeds contain underlying allelopathic compounds such as phenolic acids and ionone that act against both aquatic and terrestrial plants [70][71][72], but there is no clear evidence to support their contribution in weeding.…”
Section: Weeding Mechanism Of Duckweedmentioning
confidence: 99%